Development of plant disease detection system - Azamuddin Daud (School of Computer and Communication Engineering, University Malaysia Perlis, 2015)
This project will focus on system to detect the disease of the plant by using Matlab simulation tools. Image will be captured by using any types of camera and the system will load and process the image. Disease area on the plant will be shown after the process completed done.